2018
DOI: 10.2967/jnumed.118.212803
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Trace Metal Metabolism in Health and Disease from PET: “PET Metallomics”

Abstract: This review highlights opportunities that now present themselves, exemplified by studies of copper metabolism that are in the vanguard of a new research front in molecular imaging: "PET metallomics."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…PET with intravenous [ 64 Cu]CuCl 2 was previously evaluated in several preclinical cancer models as a potential diagnostic tool 24 . Although some studies found no correlation of intravenous [ 64 Cu]CuCl 2 uptake with CTR1 expression in cancer cells 25 , there are other works which suggest a key role of CTR1 in copper uptake and its intracellular homeostasis 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET with intravenous [ 64 Cu]CuCl 2 was previously evaluated in several preclinical cancer models as a potential diagnostic tool 24 . Although some studies found no correlation of intravenous [ 64 Cu]CuCl 2 uptake with CTR1 expression in cancer cells 25 , there are other works which suggest a key role of CTR1 in copper uptake and its intracellular homeostasis 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that CTR1 expression is important in regulating the tumor uptake of copper, but it is not the sole player. In fact, it is well known that copper levels depend also on the subcellular localization of CTR1 which can differ between tumor types, and that copper homeostasis is also regulated by copper efflux transporters ATP7A and ATP7B 24 . All these factors can influence intracellular copper levels, and this may be the reason for conflicting evidence reported on the utility of [ 64 Cu]CuCl 2 for tumor diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, currently, numerous radiotracers as 52 Fe-citrate are able to track iron particles in peculiar human pathologies such as Wilson's disease (17). Moreover, there is an increase of iron in the brain with aging and increased iron levels were observed along with deposits of senile plaque in Alzheimer patients (18). Similarly, this approach could be proposed for the screening of breast cancer patients in order to identify the lesions with high probability to develop bone lesions.…”
mentioning
confidence: 99%
“…3B). 79 PET metallomics is certainly in its infancy, but already promising 64 Cu PET studies are appearing in the literature within the context of Wilson's disease, dementia and cancer, with the potential to improve diagnostics and complement or even replace biopsies 8084…”
Section: Spectroscopy Imagingmentioning
confidence: 99%